Study of heart rate changes in different salat's positions - Ibrahim, F.; Ahmad, W.A.W. (2008)
This paper describes the changes in the heart rate (HR) for 24 healthy subjects (10 males and 14 females) during performing different Salat's positions. Salat is the muslim prayer which involve performing certain physical postures as well as spiritual act. Heart rate was measured using Schiller AT-102 augmented Electrocardiogram (ECG) at each of the following Salat's positions: standing (qiyyam), bowing (rukuk), prostration (sujud) and sitting (tashahhud) including 5 minutes resting before perfoming the Salat's positions. The result shows that the HR differs at the different Salat's positions. The HR was lowered from the standing (qiyyam) to the bowing (rukuk) position, and drops further when the subjects were in the prostration position. The HR however, increases back when subjects were in the tashahhud position. The pattern shows that the prostration position has the lowest HR value. There are many factors that have influenced those results. Â© 2008 Springer-Verlag.